Burzhinsky Pavel Vasilievich (to the 150th anniversary) - A. I. Vengerovsky (Бюллетень сибирской медицины, 2008)
Scientific biography of Pavel Vasilievich Burzhinsky, first Siberian pharmacologist, founder of Pharmacology Chair in Imperial Tomsk University — Siberian State Medical University.